Verbal Behavior in Project Team Communication - Agnieszka BURDZY; Beata GONTAR (Communications of International Proceedings, 2021)
Effective communication among the team members results in successful completion of the project, which positively influences the business relationships with the stakeholders, and as a result provides the manager and the team with more interesting and challenging projects. The main purpose of this article is to present the mechanism of verbal communication within a project team. The concept is strictly connected to a problem of information exchange in a project team. The role of a team manager includes verbal communication within a team and has influence on motivation. The research paper also contains the topics of Herzberg’s motivation theory and Brown and Levinson’s concept of super-strategies, downward mobbing and Skinner’s definition of verbal behavior. Presented results are based on the analysis of the in-depth interviews and a questionnaire conducted in selected project teams from companies of different sizes. The survey was conducted in order to find out whether verbal feedback (supportive or negative) exerts motivating or demotivating impact on the project team members.
Keywords: Communication; project management; Skinner’s verbal behavior; Brown and Levinson’s theory of politeness; super-strategies